Pengaruh Biaya Promosi dan Harga Jual terhadap Volume Penjualan pada Yamaha Agung Motor Brebes - Ahmad Faozan; Hilda Kumala Wulandari; Heru Subagja; Andi Yulianto; Slamet Bambang Riono (Journal of Accounting and Finance (JACFIN), 2019)
Companies engaged in the automotive sector, especially two-wheeled vehicles, cannot be separated from the competition. Therefore, companies are vying to increase sales volume as much as possible. This study aims to determine and analyze the effect of promotional costs on sales volume, selling prices on sales volume, and promotional costs and selling prices on sales volume. This study used secondary data. The population in this study is the annual financial report on Yamaha Agung Motor Brebes for 2016-2018. A sample of 117 data. Sample selection using purposive sampling technique. Hypothesis testing using multiple linear regression analysis, with the help of the SPSS program. The results of this study showed: promotion costs partially have a significant effect on sales volume, partial selling prices have no significant effect on sales volume, and promotion costs and selling prices simultaneously have a significant effect on sales volume